In Vivo Evaluation of Demineralized Bone Matrix with Cancellous Bone Putty Formed Using Hydroxyethyl Cellulose as an Allograft Material in a Canine Tibial Defect Model - Donghyeok Yoo; Minha Oh; Minkyung Kim; Dongbin Lee (Animals, 2024)
Demineralized bone matrix (DBM) is a widely used allograft material for bone repair, but its handling properties and retention at defect sites can be challenging. Hydroxyethyl cellulose (HEC) has shown promise as a biocompatible carrier for bone graft materials. This study aimed to evaluate the efficacy of DBM combined with cancellous bone putty formed using HEC as an allograft material for bone regeneration in a canine tibial defect model. Experiments were conducted using dogs with proximal tibial defects. Four groups were compared: empty (control group), DBM + HEC (DH), DBM + cancellous bone + HEC (DCH), and DBM + cancellous bone + calcium phosphate + HEC (DCCH). Radiographic, micro-computed tomography (CT), and histomorphometric evaluations were performed 4 and 8 weeks postoperatively to assess bone regeneration. The Empty group consistently exhibited the lowest levels of bone regeneration throughout the study period, indicating that DBM and cancellous bone with HEC significantly enhanced bone regeneration. At week 4, the DCCH group showed the fastest bone regeneration on radiography and micro-computed tomography. By week 8, the DCH group showed the highest area ratio of new bone among all experimental areas, followed by the DH and DCCH groups. This study demonstrated that HEC significantly enhances the handling, mechanical properties, and osteogenic potential of DBM and cancellous bone grafts, making it a promising carrier for clinical applications in canine allograft models. When mixed with allograft cancellous bone, which has high porosity and mechanical strength, it becomes a promising material offering a more effective and reliable option for bone repair and regeneration.